The cognitive control of memory: age differences in the neural correlates of successful remembering and intentional forgetting. - Avery A Rizio (Public Library of Science (PLoS), 2014)
Successful memory encoding depends on the ability to intentionally encode relevant information (via differential encoding) and intentionally forget that which is irrelevant (via inhibition). Both cognitive processes have been shown to decline in aging and are theorized to underlie age-related deficits in the cognitive control of memory. The current study uses the Directed Forgetting paradigm in conjunction with fMRI to investigate age-related differences in both cognitive processes, with the specific aim of elucidating neural evidence supporting these theorized deficits. Results indicate relatively preserved differential encoding, with age differences consistent with previous models of age-related compensation (i.e., increased frontal and bilateral recruitment). Older adults did display noticeable differences in the recruitment of brain regions related to intentional forgetting, specifically exhibiting reduced activity in the right superior prefrontal cortex, a region shown to be critical to inhibitory processing. However, older adults exhibited increased reliance on processing in right inferior parietal lobe associated with successful forgetting. Activity in this region was negatively correlated with activity in the medial temporal lobe, suggesting a shift in the locus of inhibition compared to the frontally mediated inhibition observed in younger adults. Finally, while previous studies found intentional and incidental forgetting to be dissociable in younger adults, this differentiation appears to be reduced in older adults. The current results are the first to provide neural evidence for an age-related reduction in processes that support intentional forgetting.